Newspaper Editorial: Genre of Rhetorical Artifact - Sharma, Bal Krishna (Haimaprabha, 2024)
Newspaper editorials are considered one of the most underrated and mundane texts. While thousands of newspapers publish editorials exerting worldwide influence, it is unfortunate that they have received least scholarly attention and study. What is, therefore, baffling is that newspaper editorials are generally regarded as taken-for-granted texts and not regarded as worthy of scholarly discussion and study. Equally despairing is the approach of common readers who treat editorial texts with an all-out indifference.Against this scenario, it is vitally important to understand how editorials operate to disseminate their contents. Although newspapers have been studied from different perspectives over the centuries, there still exists a big gap in the existing literature about the study of editorial discourse from rhetorical perspectives. While addressing this gap, the paper also aims at enhancing readers’ critical understanding of editorial texts and their rhetorical import.To examine this issue, the present article discusses emerging debates among communication scholars about the rhetorical functions and physical components of newspaper editorial texts.After surveying features that constitute a typical editorial text, this paper explores the approaches and paradigms that define editorials as genre of rhetorical artifacts.